Energy Alternatives - Friedman, Lauri S., editor 384087; Gale Group (Online service) 651863 (Detroit, MI : Greenhaven Press, 2011)
Explores the issues surrounding energy alternatives by placing opinions from a wide range of sources in a pro/con format. Features articles that express various perspectives on this topic.